KOLABORASI KEPEMIMPINAN ANTARA KEPALA SEKOLAH DAN KOMITE SEKOLAH DALAM PENGEMBANGAN SARANA DAN PRASARANA DI SMKN 1 KUPANG - Maglon Ferdinand Banamtuan; Soleman Baun (Jurnal Dinamika Pendidikan, 2021)
The objectives to be achieved in this study, namely: 1). To find out the Principal's performance in developing facilities and infrastructure for educators at the State 1 Kupang Vocational High School; and 2). To find out the performance of the School Committee in developing the facilities and infrastructure of educators at the State 1 Kupang Vocational High School. This study uses a qualitative method approach, which leads to case study research. The results of this study are: 1). Regarding the leadership of the principal include: a). think of support from other parties so that further sustainability can be carried out effectively and efficiently; b). The principal as the implementer of infrastructure development at the State 1 Kupang Vocational High School should be good at providing, planning and facilitating; c). The controller of the development of infrastructure in the State 1 Vocational High School Kupang where the principal is the top controlling leader who determines the key to the success of the school to achieve the objectives, and control at the Kupang 1 State Vocational High School is a process to continuously observe the implementation of work plans that have been prepared make corrections to irregularities in the development of the pre-existing facilities that occurred. Whereas those relating to the leadership of the school committee include: a). advisory agency in managing school facilities and infrastructure; b). Supporting agency in the management of school facilities and facilities; c). The controlling agency in the management of school facilities and infrastructure was realized in the participation of the school committee in the Keuanan Asli School Plan drafting meeting, directly checking the condition of facilities and infrastructure in the school and always being directly involved in the process of eliminating facilities and infrastructure; d). Mediator in managing school facilities and infrastructure; and e). Improving the quality of school facilities and infrastructure certainly cannot be separated from the obstacles faced. The main obstacles faced by school committees in an effort to improve the quality of facilities and infrastructure are the problem of funds and the limited land owned by the school.